2014
DOI: 10.1371/journal.pone.0108139
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile of Genes as Indicators of Developmental Competence and Quality of In Vitro Fertilization and Somatic Cell Nuclear Transfer Bovine Embryos

Abstract: Reproductive biotechnologies such as in vitro fertilization (IVF) and somatic cell nuclear transfer (SCNT) enable improved reproductive efficiency of animals. However, the birth rate of in vitro-derived embryos still lags behind that of their in vivo counterparts. Thus, it is critical to develop an accurate evaluation and prediction system of embryo competence, both for commercial purposes and for scientific research. Previous works have demonstrated that in vitro culture systems induce alterations in the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…A better knowledge about gene expression patterns during early embryo development would give an accurate evaluation and prediction system of embryo competence, both for commercial purposes and for scientific research (Cánepa et al., ). It is necessary to have a better understanding of stage‐specific gene expression because each stage of embryo is characterized by temporal and spatial activation of a specific subset of genes (Ko et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A better knowledge about gene expression patterns during early embryo development would give an accurate evaluation and prediction system of embryo competence, both for commercial purposes and for scientific research (Cánepa et al., ). It is necessary to have a better understanding of stage‐specific gene expression because each stage of embryo is characterized by temporal and spatial activation of a specific subset of genes (Ko et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…As anticipated, the homology of the cloned sheep embryo FGF2 with cattle FGF2 was very high (100% in terms of both nucleotide and amino acid sequence, respectively), whereas a lower degree of similarity was noticed between rat and mouse (69.2% and 98.2%, respectively). At nucleotide level, changes were observed from T to A better knowledge about gene expression patterns during early embryo development would give an accurate evaluation and prediction system of embryo competence, both for commercial purposes and for scientific research (Cánepa et al, 2014). It is necessary to have a better understanding of stage-specific gene expression because each stage of embryo is characterized by temporal and spatial activation of a specific subset of genes (Ko et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, revolutionary disciplines, such as transcriptomics have allowed comprehension of complex processes occurring during early development [ 33 ]. Quantification of transcripts in embryos has been used to assess embryo developmental competence in vitro and in vivo [ 34 , 35 ]. However, very few OT reports have included PCR studies to understand the interactions taking place between ooplasmic and nuclear components.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from morphological criteria, expression levels of developmentally important genes have also been monitored to assess blastocyst quality [4, 20], which may explain how baicalin improves developmental competence of mouse embryos in vitro . The level of Gja1 mRNA, which is one of the gap junction proteins, has been shown to be higher in in vivo derived mouse and bovine blastocysts compared to those produced in vitro [15, 28], which is consistent with the higher quality blastocysts recorded in terms of cryotolerance [29].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been reported that in vitro culture conditions can lead to increased incidence of cellular stress and apoptosis [15, 16] and induce aberrant DNA methylation in mouse embryos [17, 18], both of which may result in decreased blastocyst quality and even affect the viability of offspring after transfer into a surrogate. Gene expression analysis, a preferred method over conventional criteria like embryo morphology and developmental rates [19], has commonly been used to assess embryo quality and to optimize in vitro culture conditions [20]. Therefore, in this study, a group of marker genes related to cellular stress and apoptosis, and DNA methylation were measured to explore the regulatory mechanism of baicalin in developmental competence of mouse embryos in vitro .…”
mentioning
confidence: 99%